## Simplifying (x³ × x²)^5

This expression involves several exponent rules, which we'll use to simplify it.

### Step 1: Simplify the expression inside the parentheses

**Rule:**When multiplying exponents with the same base, you add the powers.**Applying the rule:**(x³ × x²) = x^(3+2) = x⁵

### Step 2: Apply the exponent outside the parentheses

**Rule:**When raising a power to another power, you multiply the exponents.**Applying the rule:**(x⁵)⁵ = x^(5*5) = x²⁵

### Conclusion

Therefore, the simplified form of (x³ × x²)^5 is **x²⁵**.